2016
DOI: 10.1016/j.fertnstert.2015.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Bowel occult microscopic endometriosis in resection margins in deep colorectal endometriosis specimens has no impact on short-term postoperative outcomes

Abstract: NCT02294825.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Mabrouk et al also reported no differences in SF‐36 scores between patients who underwent shaving or resection surgery . Furthermore, in our study, postoperative GIQLI scores obtained for the two groups remained below normal values (score: 125) , consistent with those obtained by Roman et al , with the GIQLI score in the SG far higher than in the RG. Though no preoperative evaluation using a QoL questionnaire was undertaken by the authors, these data suggest that after radical surgery, digestive symptoms continue to affect QoL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mabrouk et al also reported no differences in SF‐36 scores between patients who underwent shaving or resection surgery . Furthermore, in our study, postoperative GIQLI scores obtained for the two groups remained below normal values (score: 125) , consistent with those obtained by Roman et al , with the GIQLI score in the SG far higher than in the RG. Though no preoperative evaluation using a QoL questionnaire was undertaken by the authors, these data suggest that after radical surgery, digestive symptoms continue to affect QoL.…”
Section: Discussionsupporting
confidence: 90%
“…Though no preoperative evaluation using a QoL questionnaire was undertaken by the authors, these data suggest that after radical surgery, digestive symptoms continue to affect QoL. Radical resection fails to provide a solution to all digestive symptoms, due most likely to their multifactorial origin beyond the lesion itself .…”
Section: Discussionmentioning
confidence: 91%
“…However, bowel occult microscopic endometriosis (BOME) in resection margins was analyzed in a study performed by Roman et al on 103 patients managed by colorectal resection for DIE. The authors compared the rates of dyschezia, diarrhea, constipation, bloating and overall values of GIQLI and KESS scores at 1 year and 3 years postoperatively and demonstrated no statistical significance between women with and without BOME (found in 14% of specimen resection margins) (13) .…”
Section: Discussionmentioning
confidence: 98%
“…reported that the recurrence rate of pelvic endometriosis was 15% after 8 years . Bowel occult microscopic endometriosis was noted in 14.6% of specimen resection margins . Therefore, long‐term follow‐up to monitor for postoperative recurrence and residual lesions is necessary.…”
Section: Discussionmentioning
confidence: 99%